A Special Role of Boolean Quadratic Polytopes among Other Combinatorial Polytopes - A. N. Maksimenko (Моделирование и анализ информационных систем)
We consider several families of combinatorial polytopes associated with the following NP-complete problems: maximum cut, Boolean quadratic programming, quadratic linear ordering, quadratic assignment, set partition, set packing, stable set, 3-assignment. For comparing two families of polytopes we use the following method. We say that a family